Advanced shooting target with bullet collector, semi-automatic bulls-eye paper positioning and automatic shooting score - Hendriana, Dena; Umniyati, Yunita; Soonggalon, Erikson Ferry; Averino, Isaac Hansen; Gartina, Mohammad Rizky; Aryo, Rakhmad; Iwan, Iwan; Yahya, Prima Kharisma Indra (SINERGI, 2025)
Shooting exercises in Indonesia typically use simple bulls-eye targets on wooden boards with sand backstops, requiring manual setup and score calculation. This setup is inefficient, especially for long-range shooting, as operators must walk far to retrieve targets, and bullets embedded in sand are hard to recycle. This project developed an advanced shooting target featuring a bullet collector, semi-automatic target setup, automatic scoring, and target monitoring. A system with such complete features is not available in the market. This target system has a roll of bulls-eye paper and the roller is powered by a servo motor controlled by a switch to command a fresh new page of bulls-eye its positioning is helped by an infrared sensor to detect markers in the paper for correct positioning. This system is equipped with a bullet collector system by directing the bullet to a container using 450 angled armor and a layer of sand in the container to stop the bullet. This system is also equipped with a camera pointing to the bulls-eye paper and its output is transmitted to a monitor close to the shooter to identify bullet tracks for evaluating his shooting performance and to improve his shooting strategy. The image from the same camera is used for image processing with the OpenCV library and Python scripts to calculate the shooting score automatically. Several physical tests have been conducted and the system proves to perform reasonably well in the tests with some errors of around 3% for single bullet holes and simple multiple bullet holes. Based on test results, the pistol bullets have quite different properties from the rifle bullets. Pistol bullets follow the impact deflection with a coefficient of restitution e = 0 while rifle bullets follow the impact deflection with e ≈ 0.5. The pistol bullets are completely disintegrated after impact while the rifle bullets are just distorted.